Analysis of Factors Affecting the Human Development Index in Regencies/Municipalities of Banten Province in 2020–2024 - Deris Desmawan; Rizal Syaifudin; Ewing Yuvisa Ibrani (PT. EQUATOR SINAR AKADEMIA, 2026)
This study aims to analyze the factors affecting the Human Development Index in regencies and municipalities of Banten Province during 2020–2024. The dependent variable in this study is the Human Development Index, while the independent variables include Poverty Rate, Population Density, Labor Force Participation Rate, Life Expectancy, District/City Minimum Wage, and Environmental Quality Index. This study uses secondary data in the form of panel data covering 8 regencies/municipalities in Banten Province during the 2020–2024 period. The analytical method employed is panel data regression, with the Random Effect Model selected as the best model. The results show that, partially, only Life Expectancy has a positive and significant effect on the Human Development Index. Meanwhile, Poverty Rate and Environmental Quality Index have negative but insignificant effects, while Population Density, Labor Force Participation Rate, and District/City Minimum Wage have positive but insignificant effects. Simultaneously, all independent variables affect the Human Development Index. The overall R-squared value of 0.8583 indicates that the independent variables explain 85.83 percent of the variation in the Human Development Index.